High Performance Work System (HPWS) and Teacher's Innovative Work Behavior: The Role of Proactive Behavior - Julita; Muhammad Rasyid Abdillah; Ali Asfar (SAINS ORGANISASI, 2023)
This study aims to determine the effect of the High-Performance Work System (HPWS) on the innovative work behavior of elementary school teachers with the role of the teacher's proactive behavior as mediation. There were 63 elementary school teachers in Pekaian District who worked for a minimum of 1 year as respondents in the study. Sampling was carried out using the convenience sampling method and analysis techniques using Structural Equation Modeling (SEM) with the help of the WarpPls 8.0 program. This study shows the results that the High-Performance Work System (HPWS) has a positive but not significant effect on the innovative work behavior of elementary school teachers in Pekaian District, while the High-Performance Work System (HPWS) has a positive and significant effect on teacher proactive behavior, and teacher proactive behavior has a positive effect and significant to the teacher's innovative work behavior. The role of the teacher's proactive behavior is able to mediate part of the relationship between the High-Performance Work System (HPWS) and the innovative work behavior of elementary school teachers in Pekaian District. The managerial implication of this research is that school principals must be able to motivate teachers to increase their proactive behavior and to improve the High-Performance Work System (HPWS) of the schools they lead so that they can increase teachers' innovative work behavior